TEKNOLOGI PRODUKSI DAN APLIKASI MIKROBA PELARUT HARA SEBAGAI PUPUK HAYATI - Ida Nursanti (Jurnal Media Pertanian, 2017)
AbstractThe use of biological fertilizer can increase the amount of microorganisms and accelerates the process of mikrobologis, increase the availability of nutrient, nutrient absorption, pressed activate soil-borne disease, speed up the composting process, improve soil structure, and generate active substance that can increase the pertumbuhandan of development of the plant. Types of Microbes as biological fertilizer raw material among other bacteria and mushrooms or fungi. Solvent fospat bacteria is having bacteria consume simple carbon compounds, such as root exudate and the rest of the plant. Mycorrhiza fungi as the root of a plant helps to absorb the nutrient elements especially nutrient phosphate. Factors that determine the quality of biological fertilizer is the number of microorganisms. Storage at low temperature is generally more suited to survival of microorganisms, moisture, the death of the microorganism can be reduced. Microbes sensitive to direct sunlight. Production technology which has been successfully applied is engineering techniques and mikroenkapsulasi cell fermentation microbes. Biological fertilizer nutrient solvent products that have been produced; Biological fertilizer Enchancing Microbial Activities in The Soils, Sustainable, Bio-Tiens Golden Harvest, Plus Biological Fertilizer and Migra Bio-phosphate.Keywords: biodiversity, Fertilizer production technology. AbstrakPenggunaan pupuk hayati dapat meningkatkan jumlah mikroorganisme dan mempercepat proses mikrobologis, meningkatkan ketersediaan hara, mengaktifkan serapan hara, menekan soil-borne disease, mempercepat proses pengomposan, memperbaiki struktur tanah, dan menghasilkan substansi aktif yang dapat meningkatkan pertumbuhandan perkembangan tanaman. Jenis Mikroba sebagai bahan dasar pupuk hayati antara lain bakteri dan cendawan atau fungi. Bakteri pelarut fospat merupakan bakteri dekomposer yang mengkonsumsi senyawa karbon sederhana, seperti eksudat akar dan sisa tanaman. Mikoriza sebagai jamur akar membantu tanaman untuk menyerap unsur hara terutama unsur hara fosfat. Faktor yang menentukan mutu pupuk hayati adalah jumlah mikroorganisme. Penyimpanan pada suhu rendah umumnya lebih cocok untuk ketahanan hidup mikroorganisme, mempertahankan kelembaban, kematian mikroorganisme dapat dikurangi. Mikroba  peka terhadap sinar matahari langsung. Teknologi produksi yang telah berhasil diterapkan adalah rekayasa fermentasi dan teknik mikroenkapsulasi sel mikroba.  Produk pupuk hayati pelarut hara yang telah dihasilkan ; Pupuk Hayati Enchancing Microbial Activities in The Soils, Bio-Lestari, Tiens Golden Harvest, Migra Plus dan Pupuk Hayati Bio-fosfat.Kata kunci : Pupuk hayati, teknologi produksi.